(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Vitamin D Deficiency is a world-wide problem and it is defined as 25(OH)D3 level below 20 ng/ml. It contributes skeletal and non-skeletal health effects. Musculo-skeletal abnormalities along with non-skeletal health effects such as microbial infection, cardiovascular disorders, cancers, autoimmune diseases, asthma and allergy, endocrine and metabolic diseases, mental health etc are seen in Vitamin D deficiency. Vitamin D deficiency or insufficiency is mostly under diagnosed or under attention topics or unaware matter to general population. It is mostly preventable and treatable condition that needs due attention to life-style modification, medication, self-awareness and campaign and further research. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 78-83